A Novel Peptide-Based SILAC Method to Identify the Posttranslational Modifications Provides Evidence for Unconventional Ubiquitination in the ER-Associated Degradation Pathway. (3rd February 2013) - Anania, Veronica G.; Bustos, Daisy J.; Lill, Jennie R.; Kirkpatrick, Donald S.; Coscoy, Laurent
Abstract : The endoplasmic reticulum-associated degradation (ERAD) pathway is responsible for disposing misfolded proteins from the endoplasmic reticulum by inducing their ubiquitination and degradation. Ubiquitination is conventionally observed on lysine residues and has been demonstrated on cysteine residues and protein N-termini. Ubiquitination is fundamental to the ERAD process; however, a mutant T-cell receptor α (TCR α ) lacking lysine residues is targeted for the degradation by the ERAD pathway. We have shown that ubiquitination of lysine-less TCR α occurs on internal, non-lysine residues and that the same E3 ligase conjugates ubiquitin to TCR α in the presence or absence of lysine residues. Mass-spectrometry indicates that WT-TCR α is ubiquitinated on multiple lysine residues. Recent publications have provided indirect evidence that serine and threonine residues may be modified by ubiquitin. Using a novel peptide-based stable isotope labeling in cell culture (SILAC) approach, we show that specific lysine-less TCR α peptides become modified. In this study, we demonstrate that it is possible to detect both ester and thioester based ubiquitination events, although the exact linkage on lysine-less TCR α remains elusive. These findings demonstrate that SILAC can be used as a tool to identify modified peptides, even those with novel modifications that may not be detected using conventional proteomic work flows or informatics algorithms.